Letter: screening for adrenal suppression in paediatric inflammatory bowel disease. Issue 8 (3rd October 2018) - Wood, P.; Henderson, P.
Abstract : Linked Content This article is linked to Philpott et al papers. To view these articles visit https://doi.org/10.1111/apt.14573 and https://doi.org/10.1111/apt.14954 .